Formulation of Niosomal Gel for Enhanced Transdermal Lornoxicam Delivery: In-Vitro and In-Vivo Evaluation - El-Ridy, Mohamed S.; Yehia, Soad Aly; Mohsen, Amira Mohamed; El-Awdan, Sally A.; Darwish, Asmaa Badawy (Current Drug Delivery, 2018)
Background: The objective of this study was to investigate the potential of niosomal gels as a transdermal delivery system to improve the permeation and anti-inflammatory activity of Lornoxicam (LX). Methods: LX niosomes were prepared by thin film hydration technique and were characterized using Transmission Electron Microscopy (TEM), Differential Scanning Calorimetry (DSC), Particle Size analysis and Zeta potential determination. LX niosomal gel/LX loaded gel were prepared using Carbopol 934 (2%) and were evaluated for their physical appearance, pH and rheological behaviour. Ex vivo skin permeation test was performed on dorsal region of wistar rats. In vivo studies comprised skin irritation test and anti-inflammatory activity study. Results: The prepared LX niosomes exhibited an entrapment efficiency of more than 66% and a particle size diameter ranging from 295 nm to 1298 nm, with negatively charged zeta potential. TEM electron micrographs revealed spherical shaped vesicles. The release pattern of drug was analyzed and found to follow Higuchi's model. Rheology studies revealed the pseudoplastic behaviour of LX niosomal gel. They exhibited a one and half fold increase in drug permeated through rat skin, when compared to free drug. Skin irritation test proved the non-irritancy of LX niosomal gels, when applied to dorsal region of Wistar rats. Percentage edema inhibition of LX niosomes was significantly higher (P<0.05) than that of free LX group showing an enhanced anti-inflammatory activity of LX niosomes. Conclusion: These findings revealed that LX loaded niosomal gels could be a potential transdermal drug delivery system.
Keywords: niosomal gel